Correlation of focal neuroendocrine differentiation in prostate cancer with the parameters of predictive value - Mijovic, Milica Lj; Ćorac, Aleksandar; Smiljić, Sonja; Savić, Sladjana; Mandić, Predrag; Vitković, Leonida; Leštarević, Snežana; Janićijević Hudomal, Snežana (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Neuroendocrine (NE) cells are one of the epithelial populations in the prostate. It is well-known that the focal neuroendocrine differentiation (FNED) in prostate cancer (PC) is an aggressive subtype that most commonly evolves from preexisting PC which does not respond to hormone therapy (androgen independed PC). The incidence and clinical importance of FNED in PC is not clearly understood because of conflicting results in the studies, and evaluation of FNED is not routinely performed in clinical practice. The aim of the present study is to determine the importance of FNED presence in the examined prostate changes with special reference to the relationship of FNED degree in PC with some parameters of predictive value [Gleason score, preoperative serum total prostata specific antigen (PSA) value, tumor volume and tumor stage]. Methods. The study included the biopsy material from 100 untreated consecutive prostate pathological changes: 70 PC, 20 prostatic intraepithelial neoplasia (PIN) and 10 benign prostatic hyperplasia (BPH). The patients with PIN and BPH were the control groups. A block containing part of the main bulk of pathological change was chosen as representative based on hematoxylin-eosin appearance, and a section of this block was immunohistochemically stained for the tissue PSA (to mark prostatic secretory cells) and chromogranin A, serotonin and synaptophysin (to mark NE cells). Results. We found a very pronounced degree of FNED differentiation in 16 (22.9%) PC. Ten (62.5%) of them had Gleason score ≥ 7, the average serum PSA level was 32.62 ± 30.80 ng/mL, average tumor volume was 43.18 ± 31.45 mL and 6 (37.5%) of this PC were detected in D clinical stage with distant hematogenous metastases. The FNED is negatively correlated with the serum PSA level, Gleason score and clinical stage positively correlated with the tumor volume, but without statistically significant differences. Conclusion. The FNED has no significant role in the prognosis of PC.
Keywords: prostatic neoplasms; neuroendocrinology; prostate-specific antigen; risk factors; neoplasm staging; prognosis